The effect of compression socks worn during a marathon on hemostatic balance - Zaleski, A. L.; Ballard, K. D.; Pescatello, L. S.; Panza, G. A.; Kupchak, B. R.; Dada, M. R.; Roman, W.; Thompson, P. D.; Taylor, B. A. (The Physician and Sportsmedicine, 2015)
Marathon running evokes parallel increases in markers of coagulation and fibrinolysis (i.e. hemostatic activation) immediately following strenuous, endurance exercise such that hemostatic balance is maintained. However, other factors incident to marathon running (i.e. dehydration, travel) may disproportionately activate the coagulatory system, increasing blood clot risk after an endurance event in otherwise healthy individuals. We investigated the effect of compression socks on exercise-induced hemostatic activation and balance in endurance athletes running the 2013 Hartford Marathon. Methods. Adults (n = 20) were divided into compression sock (SOCK; n = 10) and control (CONTROL; n = 10) groups. Age, anthropometrics, vital signs, training mileage and finishing time were collected. Venous blood samples were collected 1 day before, immediately after and 1 day following the marathon for analysis of coagulatory (i.e. thrombin-antithrombin complex [TAT] and D-dimer) and fibrinolytic (i.e. tissue plasminogen activator [t-PA]) factors. Results. Plasma D-dimer, TAT and t-PA did not differ between groups at baseline (p > 0.16). There were no significant group · time interactions (all p = 0.17), however, average t-PA was lower in SOCK (8.9 ± 0.7 ng/mL) than CONTROL (11.2 ± 0.7 ng/mL) (p = 0.04). Average TAT also tended to be lower in SOCK (2.8 ± 0.2 µg/L) than CONTROL (3.4 ± 0.2 µg/L) (p = 0.07). Conclusions. Our results suggest that overall hemostatic activation (both coagulation and fibrinolysis) following a marathon tended to be lower with compression socks. Thus, compression socks do not adversely influence markers of hemostasis, appear safe for overall use in runners and may reduce exercise-associated hemostatic activation in individuals at risk for deep vein thrombosis.